Desenvolvimento, implementação e avaliação de uma estação agrohidrometeorológica automática e sensores ambientais - Canafistula, Francisco José Firmino (2013)
Access to water resources creates conflicts in all regions of the world. With the increase in consumption and water scarcity, the tendency is to increase water insecurity and conflict, therefore it is essential and necessary to develop tools, instruments and measurement methodologies that increase the efficiency and consistency of studies of the management of this resource. The technological development of a system for automatic collection and storage of meteorological and hydrological data is presented in this thesis. The text also describes the development, methodology, calibration, installation and evaluation of operation, in the experimental field, of sensors with special features. The focus of the development and evaluation of the sensors is to meet the uncertainties of changing space-time weather data from the semi-arid Northeast. Sought in the microcontroller technology development system of data acquisition, because its range of architectures and the low costs. Part of the sensors has developed technology on based industrial transducers and semiconductors. The range of the value of the dielectric constant of water, coupled with the operating model of the capacitors also produced transducers in this work. It was possible to make the measurement and storage of environmental data from these micro-watersheds in the semiarid and thus present the relationship between weather events (rainfall) and hydrological (flow of courses in a second order semi-arid region). Relative humidity, air temperature, soil temperature and soil moisture values were also monitored by the probes developed. Test instruments is necessary because it allows improving the accuracy and robustness of the data obtained by the system. The system has allowed to the construction of hydrographs of micro-basins. The communication channel of the system was efficient in data collection, however, it is necessary to establish alternative means of connectivity for better evaluation and system maintenance. Research on performance of capacitive automatic rain gauge in laboratory and field demonstrated the ability of the instrument to measure all parameters of rainfall. Events with in 0.7 mm range can be measured, including rainfall intensity